Constructing a hierarchy project model to purchase medical information systems. Issue 6 (5th May 2009) - Hsu, Pi-Fang; Chang, Che-Wei; Wu, Cheng-Lung
This study developed project purchase medical information system model in this comprises two stages. In the first stage, the Analysis Hierarchy Process (AHP) and Grey Relational Analysis (GRA) are used to determine the relative weights. In the second stage, the modified Delphi technique is used to identify the most appropriate purchase criteria, and then the Analytic Network Process (ANP) theory is applied to determine the objective weight values. The proposed model can provide primary clinic administrators with a decision-making and purchase criteria that actively encourage the medical sector outsource to information technology contractors.